2021
DOI: 10.1007/s10639-021-10535-x
|View full text |Cite
|
Sign up to set email alerts
|

Do teamwork experience and self-regulated learning determine the performance of students in an online educational technology course?

Abstract: This study uses the quantitative research approach to examine the connection between students’ teamwork experience, self-regulated learning, technology self-efficacy, and performance in an online educational technology course. Sixty-three (63) students participated in this study. The study data were collected through an online questionnaire that included background information, course satisfaction, motivation strategies for learning, and online technology self-efficacy, to study the variables’ interactions usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…For the quantitative strand of the study, a course satisfaction survey was conducted. The survey was adapted from Course Satisfaction Questionnaire (CSQ; Frey et al, 2003 ; Oyelere et al, 2021 ). According to previous studies, the CSQ was reliable and internally consistent with a Cronbach’s alpha of ~0.97 ( Wang et al, 2013 ; Oyelere et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the quantitative strand of the study, a course satisfaction survey was conducted. The survey was adapted from Course Satisfaction Questionnaire (CSQ; Frey et al, 2003 ; Oyelere et al, 2021 ). According to previous studies, the CSQ was reliable and internally consistent with a Cronbach’s alpha of ~0.97 ( Wang et al, 2013 ; Oyelere et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The survey was adapted from Course Satisfaction Questionnaire (CSQ; Frey et al, 2003 ; Oyelere et al, 2021 ). According to previous studies, the CSQ was reliable and internally consistent with a Cronbach’s alpha of ~0.97 ( Wang et al, 2013 ; Oyelere et al, 2021 ). In the present study, the Cronbach’s alpha value of the survey was 0.96.…”
Section: Methodsmentioning
confidence: 99%
“…Mathur et al (2019) proposed that teachers and other educationists should regulate the usage of FSNP to guarantee optimum utilization of the platform academic purposes and improved academic achievement. In a related study to examine the connection between students' teamwork experience, self-regulated learning, technology self-efficacy and performance in an online educational technology course, Oyelere, Olaleye, Balogun, and Tomczyk (2021) emphasized on the need to regulate time learners spend online. Oyelere et al (2021) observed that right self-regulated learning strategies in online courses motivate students to strive for a good teamwork experience, leading to increased interest in online learning and increased academic achievement.…”
Section: Introductionmentioning
confidence: 99%
“…In a related study to examine the connection between students' teamwork experience, self-regulated learning, technology self-efficacy and performance in an online educational technology course, Oyelere, Olaleye, Balogun, and Tomczyk (2021) emphasized on the need to regulate time learners spend online. Oyelere et al (2021) observed that right self-regulated learning strategies in online courses motivate students to strive for a good teamwork experience, leading to increased interest in online learning and increased academic achievement. Similarly, while Alwreikat, Zaid, and Shehata (2021) in a study to investigate the determinants of Facebook use among students and its impact on collaborative learning hold the opinion that the more time spend on FSNP the better learner academic achievement students achieve, the learning activities should be closely monitored by the tutors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation